Chikungunya virus requires an intact microtubule network for efficient viral genome delivery - Hoornweg, Tabitha E.; Bouma, Ellen M.; van de Pol, Denise P.I.; Rodenhuis-Zybert, Izabela A.; Smit, Jolanda M. (PLOS Neglected Tropical Diseases, 2020)
Author summary Chikungunya virus (CHIKV) is an alphavirus that is transmitted to humans by infected mosquitoes. Disease symptoms can include fever, rash, myalgia, and long-lasting debilitating joint pains. Unfortunately, there is currently no licensed vaccine or antiviral treatment available to combat CHIKV. Understanding the virus:host interactions during the replication cycle of the virus is crucial for the development of effective antiviral therapies. In this study we elucidated the trafficking behavior of CHIKV particles early in infection. During cell entry, CHIKV virions require an intact microtubule network for efficient delivery of the viral genome into the host cell thereby increasing the chance to productively infect a cell.